Assessing conservation measures for five Southern African endemic shark species - Cottrant, Emy (Department of Biological Sciences, 2025)
The South African coast has one of the greatest diversity of Chondrichthyan species in the world with more than 190 species recorded, including 111 species of sharks. Many of these species are endemic to southern Africa (defined as the coastlines of Namibia, South Africa and Mozambique) but are poorly studied, despite their classifications of concern according to the International Union for the Conservation of Nature (IUCN) Red List. However, South Africa continues its efforts to protect the marine environment with a network of 42 Marine Protected Areas established; the Second National Plan for the Protection of Sharks was published in 2022. Sharks, which are characterized by slow growth and maturity at an advanced age, have undergone a rapid decrease in population sizes due to overfishing and habitat loss since the 1970s. To help fill the knowledge gap on endemic shark species, I used long-term datasets to study movement ecology and behaviour in marine protected areas. Study species are dark shyshark Haploblapharus pictus, puffadder shyshark Haploblepharus edwardsii, pyjama shark Poroderma africanum, leopard catshark Poroderma pantherinum and spotted gully shark Triakis megalopterus. Datasets were composed of non-lethal sampling comprised of mark-recapture, baited remote underwater videos (BRUVs) and acoustic telemetry. Results are then used to assess current protection status of those species and give advice to adapt management policies. The analysis of capture-recapture data made it possible to determine the distribution areas of each species in the study area as well as the differences in the size and location of these areas between different sexes and maturities. The efficacy of an MPA was discussed for the protection of those species, especially relevant for the puffadder shyshark, classified as “Endangered” on the IUCN Red List. Furthermore, a comparison between growth rate of wild and captive pyjama sharks helped assessing if captive data can be transposed to wild population in order to study endangered species. Study of the movements of T. megalopterus along the coasts of the Western Cape revealed that this species does not specifically use marine protected areas, regardless of sex or sexual maturity. This characteristic suggests that in the future, if the population declines, which is a potential consequence of being caught as bycatch in longline fisheries, it would be difficult for this population to recover. We also attempted to classify the different areas used by spotted gully sharks in order to identified priority areas for conservation such as nursery areas. The analysis of the BRUVs revealed that the classic analysis techniques were sometimes not adequate to study the relationships between species. The majority of published analyzes are based on MaxN, an estimate of the abundance of each species, often to estimate the effectiveness of marine protected areas and sometimes by extrapolating on the relationships between species within the food chain. During this project, we tested a new alternative metric (visual co-occurrence) that could be included in future analyzes of this type of video, the goal being to obtain a more refined view of reality and potentially increase knowledge about the role that a specific species plays within the ecosystem. Overall, the combination of the databases analysed during this project made it possible to increase knowledge on five endemic species of South Africa and southern Africa, specifically on their movement and differences between sexes in habitat use. The protection measures in place remain effective in maintaining these populations but, like H. edwardsii, do not allow these species to grow in abundance and thus change their IUCN status. In addition, a potential future decline for these populations due to global warming or anthropogenic impact, causing habitat loss, could be fatal for these species without specific protection measures for each species. Since 2022, several projects aim to increase the area of coastal zone covered by marine protected areas in South Africa, so the results of this study have a direct impact on future conservation and management measures for these species.